Private Well Water Practices Among Environmental Health Professionals in Kansas. - Ablah, Elizabeth; Winston Marrow, Mary; Brown, Jack; Green, Sarah; Konda, Kurt; Gallagher, Lisa; Lee, Carla A. (Journal of Environmental Health, 2019)
There are significant regulatory gaps that affect 43.5 million people in the U.S. who rely on groundwater from private water wells for their drinking water. Although some local environmental health agencies provide support to private water well owners, individual private water well owners must protect themselves. This study assessed the local practices of environmental health professionals in Kansas regarding private water wells. An 18-item survey was distributed to all 61 members of the Kansas Environmental Health Association in 2016. A 90% survey response rate was achieved. In local Kansas communities, sampling of private well water occurs most frequently as a result of a homeowner's request (57%) or at the time of a real estate transaction (54%). Nearly one third of respondents reported that their jurisdictions neither inspect wells nor sample well water. Most respondents indicated their organizations did not have the capability to analyze samples for common contaminants such as pesticides (76%) or volatile organic compounds (71%). In Kansas, there appears to be a lack of uniformity in inspection, sampling, and analysis practices and policies for private water wells. Additional research is needed to determine if these results are consistent across the U.S.